2021
DOI: 10.1111/nmo.14084
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction proteins in the small intestine and prefrontal cortex of female rats exposed to stress of chronic isolation starting early in life

Abstract: Background: Simultaneous evaluation of barrier protein expression in the gut and the brain and their modulation under stress conditions have not been studied before now. As the permeability and function of the gut and blood-brain barrier are different and both express the MRs, we hypothesized that stress of post-weaning social isolation induces changes in tight junction protein expression in the gut which are (1) independent of changes in the brain and (2) are mediated via the mineralocorticoid receptor (MR).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…In a study conducted on rats with sepsis, serum claudin‐5 level was found to be lower than the control group 28 . There are many studies reporting decreased claudin‐5 gene expression in the intestine in the presence of various stressors 29–31 . Although the lack of claudin‐5 gene expression in the intestines does not exactly indicate the decrease of claudin‐5 levels in serum, it can be thought that there is an inverse relationship between low serum claudin‐5 level and intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted on rats with sepsis, serum claudin‐5 level was found to be lower than the control group 28 . There are many studies reporting decreased claudin‐5 gene expression in the intestine in the presence of various stressors 29–31 . Although the lack of claudin‐5 gene expression in the intestines does not exactly indicate the decrease of claudin‐5 levels in serum, it can be thought that there is an inverse relationship between low serum claudin‐5 level and intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“… 28 There are many studies reporting decreased claudin‐5 gene expression in the intestine in the presence of various stressors. 29 , 30 , 31 Although the lack of claudin‐5 gene expression in the intestines does not exactly indicate the decrease of claudin‐5 levels in serum, it can be thought that there is an inverse relationship between low serum claudin‐5 level and intestinal permeability. Lower levels of serum claudin‐5 in the SARS‐CoV‐2 infection group in our study may be due to the stress of the disease on the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature connects aberrant gut-brain axis signaling in MDD, nevertheless, a direct link between gut permeability and BBB leakiness, facilitating passage of circulating inflammatory mediators into the brain in this context is still debated 1 . The BBB and gut barrier had not been compared directly until a recent evaluation of female rats facing social isolation stress, which demonstrated shared modifications to Ocln, Tjp1 and Cldn5 gene expression in the prefrontal cortex and the ileum 43 . Considering our recent work identifying sex-specific BBB tight junction changes in response to social defeat 12,14 and variable stress 14 , we examined how these models influence gut integrity.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 45 Stress-induced increase in gut permeability results in increased levels of lipopolysaccharide (LPS) and inflammatory cytokines, an effect that is reversed by probiotics. 46 Importantly, in addition to affect the gut microbiome, early-life stress produces a decreased expression of tight junction expression in the gut, 47 , 48 leading to persistent increase gut permeability, 26 , 49 which allows for systemic leakage of bacteria products, such as LPS, 45 proinflammatory cytokines, 50 , 51 and bacterial translocation from the gut. 52 Since LPS, inflammatory cytokines and bacteria act directly on nociceptors to decrease nociceptive threshold and increase neuronal excitability, 53 58 since early-life stress-induced increased gut permeability persists in to adulthood, 59 leakage of LPS, cytokines and/or bacteria could contribute to hyperalgesia seen in adult NLB rats.…”
Section: Discussionmentioning
confidence: 99%